2012
DOI: 10.1007/s00253-012-4410-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of salt-induced 2-Cys peroxiredoxin from Oryza sativa increases stress tolerance and fermentation capacity in genetically engineered yeast Saccharomyces cerevisiae

Abstract: Peroxiredoxins (Prxs), also termed thioredoxin peroxidases (TPXs), are a family of thiol-specific antioxidant enzymes that are critically involved in cell defense and protect cells from oxidative damage. In this study, a putative chloroplastic 2-Cys thioredoxin peroxidase (OsTPX) was identified by proteome analysis from leaf tissue samples of rice (Oryza sativa) seedlings exposed to 0.1 M NaCl for 3 days. To investigate the relationship between the OsTPX gene and the stress response, OsTPX was cloned into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 38 publications
6
24
0
Order By: Relevance
“…There were no obvious differences in growth between two strains under low concentration (0.2 mM). An elevated concentration of 3 mM could inhibit the growth of the control strain 423 significantly, while strain TPX1 had been less affected, which was in line with the results reported by Kim et al [29]. Consequently, an enhanced tolerance of S. cerevisiae 280 with a normally functioning KmTPX1 gene provided a good foundation for further analysis and validation of other possible functions.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…There were no obvious differences in growth between two strains under low concentration (0.2 mM). An elevated concentration of 3 mM could inhibit the growth of the control strain 423 significantly, while strain TPX1 had been less affected, which was in line with the results reported by Kim et al [29]. Consequently, an enhanced tolerance of S. cerevisiae 280 with a normally functioning KmTPX1 gene provided a good foundation for further analysis and validation of other possible functions.…”
Section: Resultssupporting
confidence: 87%
“…2a), while the growth of control strain 423 had been greatly repressed on plates with 0.3 g/L of formic acid, 1.5 g/L of acetic acid, or 1.0 g/L of furfural, which was 1–2 gradients less than the strain TPX1 in the serial dilution assay. These results have been supported by a variety of similar oxidoreductases that might be contributed to the increased tolerance of S. cerevisiae to the inhibitors [815, 29]. However, despite sharing a similar mechanism of toxicity with furfural, the tolerance of TPX1 strain to 5-HMF was only slightly improved compared with the control strain.
Fig.
…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…S4C, its deletion strain no longer produced ethanol, implying the dominant role of ADH1 in ethanol biosynthesis. The evident growth advantage of ⌬adh1 could be mainly attributed to abolished synthesis of ethanol which is known to suppress cell growth and glucose uptake (33)(34)(35)(36)(37). However, glucose consumption was also reduced in ⌬adh1, suggesting possibly lowered activity of glycolysis (Fig.…”
Section: Investigation Of the Roles Of Selected Differential Proteinsmentioning
confidence: 99%
“…Molecular verification and physiological testing was then conducted on the 2Cys Prx-overexpression tobacco. Kim et al (2013) transferred the 2-Cys Prx gene from rice (Oryza sativa) into Saccharomyces cerevisiae and found that the heterologous expression of 2-Cys Prx in S. cerevisiae increased the oxidation-reduction balance in S. cerevisiae 40°C, indicating that 2-Cys Prx effectively regulates the reactive oxygen balance in organisms. H2O2 in plant cells is the intermediate product in the process of water splitting and oxygen liberation.…”
Section: Discussionmentioning
confidence: 99%